IN-VITRO CYTOTOXIC, MUTAGENIC AND GENOTOXIC EVALUATION OF TILMICOSIN - M. A. Rasheed; M. Ashraf; A. Javeed; A. A. Anjum (Journal of Animal and Plant Sciences, 2022)
The efficacy of antibiotics is endangering worldwide due to rapid development of resistant bacterial strains. It is of worth to re-evaluate previously developed antibiotics to alleviate the pressure of microbial resistance on recently developed antibiotics. In this study in vitro toxicological evaluation (cytotoxicity, mutagenicity and genotoxicity) of tilmicosin was carried out. Different concentrations (3.12, 6.25, 12.5, 25, 50, 100, 200, 400 and 800μg/mL) of tilmicosin were used. In vitro cytotoxicity was evaluated using MTT Assay. BHK-21 cells and cardiac cells from chicken embryo were used. The mutagenic potential was evaluated using Ames test. Auxotroph strains of Salmonella typhemurium (TA-98 and TA-100) were used. The genotoxicity was assessed using comet assay. Cell survival percentage of BHK-21 cells at 50μg/mL was 50.64% and IC50 was 49.64μg/mL indicating that below 49.64μg/mL all concentrations were not cytotoxic. While the cell survival percentage of chicken cardiac cells at 25μg/mL was more than 50% and at 50μg/mL was less than 50%. The IC50 calculated was 52.75μg/mL indicating that below 52.75μg/mL all concentrations are not cytotoxic for cardiac cells. The mutagenic indices of all concentrations of tilmicosin with and without S9 fraction were < 2 both for TA98 and TA100. So all the concentrations are non-mutagenic for both TA 98 and TA 100. For genotoxicity, comets were analyzed for head diameter and tail length. The damage indices were calculated. The damage was concentration dependent. The damage indices at concentrations 3.12, 6.25, 12.5 25 and 50µg/ml were not significant (P<0.01) while significant at 100, 200, 400 and 800µg/ml when compared with control (P<0.01). It may be concluded from this study that tilmicosin has not produced cytotoxicity, mutagenicity and genotoxicity at low concentrations under in vitro conditions.
Keywords: Tilmicosin; MTT Assay; Chicken cardiac cells; Ames test; Comet Assay